2014
DOI: 10.1002/ppul.23094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of nasal nitric oxide measurement in pediatric airway diseases

Abstract: Nitric oxide plays an important role in several physiological and pathophysiological processes in the respiratory tract. Different ways to measure nasal nitric oxide levels in children are currently available. The possibility of obtaining nasal nitric oxide measurement from relatively young children, combined with the availability of portable devices that can be used even in the office setting, opens new perspectives for nasal nitric oxide analysis in the pediatric daily practice. This review presents a synops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 124 publications
1
22
0
2
Order By: Relevance
“…Many of these methods require patient cooperation to exhale against a resistance or phonate to close the velum during sampling. However, quiet tidal breathing has been validated in younger children unable to cooperate [7,8,11]. Nasal NO values obtained by such tidal breath sampling has shown good reliability, sensitivity, and high within-subject repeatability [11e14].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these methods require patient cooperation to exhale against a resistance or phonate to close the velum during sampling. However, quiet tidal breathing has been validated in younger children unable to cooperate [7,8,11]. Nasal NO values obtained by such tidal breath sampling has shown good reliability, sensitivity, and high within-subject repeatability [11e14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that nNO is decreased in conditions in which the sinus becomes blocked (nasal polyps adenoidal hypertrophy), ciliary function is compromised (ciliary dyskinesia) or inducible NO synthase in the airway epithelium is reduced (cystic fibrosis) [812]. A few studies have shown nNO to be increased in AR [4, 10, 13] and one study has reported that anti-histamine treatment decreased the elevated nNO levels seen in AR patients [14]. …”
Section: Introductionmentioning
confidence: 99%
“…nNO is a non-invasive marker of inflammation that is increased in AR, and can easily be measured during a routine office visit [9, 10]. We wished to see whether nNO measurement might be useful clinically in determining AR severity and following the patient’s response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aynı zamanda ağır nazal obstrüksiyon ve primer silyer diskinezi varlığında nNO düzeyleri çok düşük ve kistik fibrozda ise orta derecede düşük bulunmaktadır (22). Bu nedenle nNO düzeyinin nazal inflamasyonun hatta AR'nin tanısında kullanılabilecek bir test olabileceği düşünülmektedir (23).…”
Section: Nazal Nitrik Oksit (Nno) öLçümüunclassified